Preferences of Indonesian Birdwatchers Toward Locations, Target Birds, and Buddies - Kurnia, Insan; Arief, Harnios; Mardiastuti, Ani; Hermawan, Rachmad (Jurnal Sylva Lestari, 2024)
Birdwatching focuses on observing wild birds. Nevertheless, previous studies were still focused on the supply aspect. Meanwhile, the demand aspect is still limited, including in Indonesia. Furthermore, understanding birdwatchers’ preferences can lead to market segmentation. Therefore, this study aimed to analyze the preferences of Indonesian birdwatchers towards location, bird targets, and buddies. Data on the demographics and preferences of Indonesian birdwatchers were collected from 1,203 respondents using an online questionnaire. Data were analyzed using Chi-Square and the Generalized Linear Model. The results revealed that most respondents prefer destinations outside the biogeographic region, with Papua being the most preferred location. Overall, birds of the Paradisaeidae family were chosen by the largest number of respondents, followed by the Accipritidae family. Variables that significantly influence the preference of birdwatching destination based on the distance taken, age, domicile, income, organization, and expertise of the birdwatchers. Locations that are further away attract young respondents who live in urban areas, have higher incomes, are members of organizations, and have high birdwatching skills. The bird species and locations preferred by the birdwatcher can be used as a basis for developing birdwatching destinations according to the birdwatcher’s preferences. Keywords: bird, birdwatching, demographic, location, preference